Discovery of small molecule antagonists of chemokine receptor CXCR6 that arrest tumor growth in SK-HEP-1 mouse xenografts as a model of hepatocellular carcinoma. Issue 4 (15th February 2020) - Peddibhotla, Satyamaheshwar; Hershberger, Paul M.; Jason Kirby, R.; Sugarman, Eliot; Maloney, Patrick R.; Hampton Sessions, E.; Divlianska, Daniela; Morfa, Camilo J.; Terry, David; Pinkerton, Anthony B.; Smith, Layton H.; Malany, Siobhan
Graphical abstract: Abstract: The chemokine system plays an important role in mediating a proinflammatory microenvironment for tumor growth in hepatocellular carcinoma (HCC). The CXCR6 receptor and its natural ligand CXCL16 are expressed at high levels in HCC cell lines and tumor tissues and receptor expression correlates with increased neutrophils in these tissues contributing to poor prognosis in patients. Availability of pharmacologcal tools targeting the CXCR6/CXCL16 axis are needed to elucidate the mechanism whereby neutrophils are affected in the tumor environment. We report the discovery of a series of small molecules with an exo -[3.3.1]azabicyclononane core. Our lead compound 81 is a potent (EC50 = 40 nM) and selective orally bioavailable small molecule antagonist of human CXCR6 receptor signaling that significantly decreases tumor growth in a 30-day mouse xenograft model of HCC.